Principles of EFL Instruction with an Islamic Perspectives - Hasibuan, Kalayo; Suryani, Neni Fitri Dwi; Jasmine, Najiyah; Pujiati, Nayata Putri; Ramadhani, Nur Ismi (Universitas Pahlawan Tuanku Tambusai, 2025)
This study examines the principles of English as a Foreign Language (EFL) instruction through the lens of Islamic perspectives. In Islamic educational contexts, EFL teaching goes beyond linguistic proficiency to also promote moral and spiritual development aligned with Islamic values. This article explores how core EFL pedagogical principles—such as meaningful learning, communicative competence, and learner-centeredness—can be integrated with Islamic values such as honesty (ṣidq), responsibility (amānah), diligence (ijtihād), and ethical behavior (adab). Through this integrated approach, EFL instruction can serve as a vehicle for character building, strengthening Islamic identity, and fostering critical intercultural awareness. The findings suggest that EFL teaching principles can be harmoniously contextualized within a holistic and transformative Islamic educational framework.